Hunger and malnutrition in Guatemala. the cultural perspective in the cooperation and development of the XXl century (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
For decades, Guatemala has deployed a wide range of development interventions aimed at strengthening food security and improving the nutritional well-being of the Guatemalan population, but the prevalence of hunger and malnutrition, especially among children, remains an unresolved problem for national and international institutions and NGOs. For this article, a critical review has been made of the production of institutional information on both state public policies and the interventions of multilateral agencies and non-governmental organizations, pointing out the cultural deficit in actions to combat malnutrition. These results have been contrasted with the main references in the scientific literature on the subject, highlighting the need to address food and nutritional security in the country with solid cultural foundations. The nature of this work and its results underline the need for an anthropological perspective and cultural studies in public policies and development actions.
Keywords: Hunger; Malnutrition; Guatemala; development; international cooperation; culture